2005
DOI: 10.1097/01.gim.0000182879.57182.b4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical testing for the nevoid basal cell carcinoma syndrome in a DNA diagnostic laboratory

Abstract: Purpose: This study determines which clinical features predict positive test results among samples submitted for DNA-based diagnostic nevoid basal cell carcinoma syndrome (NBCCS) testing, and further defines the mutational spectrum of the PTCH gene. Methods: DNA was extracted from peripheral blood leukocytes, and polymerase chain reaction products from exons 1 to 23 of the PTCH gene were directly sequenced. Pedigree phenotypic information was obtained by written questionnaire. Results: Among 106 presumably unr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 28 publications
2
40
0
1
Order By: Relevance
“…While many cases of NBCCS are inherited, sporadic occurrences are thought to account for up to 50 % of cases [7]. Although the disease is characterized by high penetrance, individuals display varying levels of expressivity even within families, sometimes making diagnosis challenging [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While many cases of NBCCS are inherited, sporadic occurrences are thought to account for up to 50 % of cases [7]. Although the disease is characterized by high penetrance, individuals display varying levels of expressivity even within families, sometimes making diagnosis challenging [5].…”
Section: Discussionmentioning
confidence: 99%
“…Under pathogenic circumstances, constitutive activation of the hedgehog signaling pathway due to mutation of critical regulatory proteins leads to tumor cell proliferation. Loss of function mutations in PTCH1, which occur by a variety of mechanisms such as deletions, insertions, and nonsense and missense mutations [7], are thought to occur in *70 % of patients who fulfill diagnostic criteria for NBCCS [15,16]. In addition, loss of function SUFU germline mutations have also been recently associated with NBCCS in a subset of cases [16].…”
Section: Molecular Pathogenesismentioning
confidence: 99%
“…Although PTCH has been identified as the gene causing NBCCS and mutations in PTCH can confirm a clinical diagnosis, molecular genetic testing has not been able to detect mutations in all affected individuals. [17][18][19][20][21] Bale et al 17,22 found that families with a history of multiple NBCCS features were more likely to have a detectable mutation; nevertheless, mutations were detected in only 40% of families tested in the study. 22 This failure to detect a mutation is likely due to the limitations of available technology, as well as the high rate of somatic mutations, rather than the presence of other causative genes.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21] Bale et al 17,22 found that families with a history of multiple NBCCS features were more likely to have a detectable mutation; nevertheless, mutations were detected in only 40% of families tested in the study. 22 This failure to detect a mutation is likely due to the limitations of available technology, as well as the high rate of somatic mutations, rather than the presence of other causative genes. More recent use of technologies such as multiplex ligation-dependent probe amplification and competitive genomic hybridization array help identify single or multiple exon deletions in PTCH that were previously undetectable by direct sequencing of exons and splice junctions.…”
Section: Discussionmentioning
confidence: 99%
“…PTCH1 gene is located on chromosome 9, in the chromosome region 9q22.32, with 24 exons streching through 70 kb (14). PTCH1 gene has one polymorphic CGG repeat marker located directly upstream of the first ATG codon of exon 1b (rs71366293) (15), and at least 48 single nucleotide polymorphisms (SNP) throughout the gene (16), 7 of them common (17).…”
Section: Introductionmentioning
confidence: 99%